Women Entrepreneurs in Small and Medium Businesses in Russia and Kazakhstan: Do Family Ties Help? - Marina Y. Sheresheva; Yury L. Vladimirov (Население и экономика)
The paper addresses the issues of the current state and prospects of women’s entrepreneurship in the modern economic environment. The purpose of the study is to provide a comprehensive assessment of women’s entrepreneurial activity and preferences in starting a business in Russia or Kazakhstan in the postCOVID-19 period and during the subsequent social and economic instability. The research was conducted using a review of theoretical literature and the descriptive and interpretive method; the empirical methodology included a questionnaire survey and transcription of respondents’ interviews, analysis of the methodological base and adaptation of the INTERGEN international project methodology, use of mathematical and statistical methods of data processing. A conceptual framework for assessing and synthesising key information from the in-depth interviews and questionnaires is proposed and tested. A number of specific characteristics, drivers and barriers to women’s entrepreneurship have been identified. In particular, it is shown that for most women entrepreneurs, the choice is driven by a desire to fulfil their potential and to find their own occupation which would bring moral satisfaction as well as income.